Sustainable Development Goals Discourse in Cultural Tourism: Financial Mechanisms for Inclusive Growth in Georgian Regions - Tamar Gamsakhurdia; Maia Gogiashvili (European Scientific Journal, ESJ, 2026)
Cultural tourism offers Georgia a strategic opportunity to advance the Sustainable Development Goals (SDGs), particularly SDG 8 (Decent Work and Economic Growth) and SDG 11 (Sustainable Cities and Communities). This study aims to identify how cultural tourism can become a financial driver for inclusive growth in Georgia's regions. The research employs a mixed-methods approach, combining quantitative and qualitative analysis. Quantitative data (2015–2024) were obtained from Geostat, the Georgian National Tourism Administration, the World Bank, and ENPARD reports to analyze revenue trends and investment levels. Qualitative data were collected through seven (n=7) in-depth semi-structured interviews with experts from the banking sector, international organizations, and small and medium-sized enterprises in the tourism industry to identify systemic financial barriers. Additionally, a comparative case study was conducted in Mtskheta and Svaneti to assess the activation of economic resources and local community participation. The findings confirm that cultural tourism in Georgia could generate an additional $100–150 million in annual revenue with the support of sustainable infrastructure and local entrepreneurship. The example of Mtskheta demonstrates a successful public-private partnership (PPP) model, where local participation increased the share of local revenues to 45%. In contrast, an analysis of Svaneti shows that, despite high demand, growth is constrained by a lack of infrastructure and limited access to financing: only 32% of local entrepreneurs utilize international grants. The study recommends the creation of regional tourism development funds and decentralized governance with local participation to ensure equitable revenue distribution and the long-term sustainability of Georgian tourism.